2021
DOI: 10.1111/ina.12906
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound emissions during HOMEChem

Abstract: Quantifying speciated concentrations and emissions of volatile organic compounds (VOCs) is critical to understanding the processes that control indoor VOC dynamics, airborne chemistry, and human exposures. Here, we present source strength profiles from the HOMEChem study, quantifying speciated VOC emissions from scripted experiments (with multiple replicates) of cooking, cleaning, and human occupancy and from unperturbed baseline measurements of the building and its contents. Measurements using a proton transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 64 publications
(192 reference statements)
7
85
1
Order By: Relevance
“…Human VOC ERs have been determined from measurements in several real-world indoor environments: a university classroom, 15 a cinema, 16 a gallery room in a museum, 17 a university athletic center, 18 a test house, 19 and laboratory offices. 20 The main VOC species measured (e.g., methanol, ethanol, monoterpenes, and siloxanes) showed large variations due to previous alcohol or food consumption and the use of personal care products.…”
Section: Introductionmentioning
confidence: 99%
“…Human VOC ERs have been determined from measurements in several real-world indoor environments: a university classroom, 15 a cinema, 16 a gallery room in a museum, 17 a university athletic center, 18 a test house, 19 and laboratory offices. 20 The main VOC species measured (e.g., methanol, ethanol, monoterpenes, and siloxanes) showed large variations due to previous alcohol or food consumption and the use of personal care products.…”
Section: Introductionmentioning
confidence: 99%
“…Another study in a university athletic center indicated that the interquartile ranges of the normalized surface emission rates (by total surface area) were 0.21–0.35, 2.1–2.9, and 0.25–0.44 μg m –2 h –1 for 6-MHO, 4-OPA and decanal, respectively, while the normalized net surface emission rates in the office were 0.42–3.10, 0.12–3.5, and 0.31–1.29 μg m –2 h –1 , respectively. A recent study in a residential test house, which has a floor area similar to the office, exhibited relatively low emissions during unoccupied periods with mean emission rates of 105, 152, and 141 μg h –1 for 6-MHO, 4-OPA, and decanal, respectively . Although volatile precursors (e.g., GA, 6-MHO) and condensed-phase skin oils can transfer to indoor surfaces via absorptive partitioning, , direct contact, and desquamation, such high emission rates from indoor surfaces in the office are unlikely attributable to heterogeneous reactions between O 3 and condensed-phase precursors on indoor surfaces.…”
Section: Resultsmentioning
confidence: 95%
“…A recent study in a residential test house, which has a floor area similar to the office, exhibited relatively low emissions during unoccupied periods with mean emission rates of 105, 152, and 141 μg h −1 for 6-MHO, 4-OPA, and decanal, respectively. 50 Although volatile precursors (e.g., GA, 6-MHO) and condensed-phase skin oils can transfer to indoor surfaces via absorptive partitioning, 51,52 direct contact, and desquamation, 44 such high emission rates from indoor surfaces in the office are unlikely attributable to heterogeneous reactions between O 3 and condensed-phase precursors on indoor surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Indoors, acrolein is known to be mainly formed through thermal processes, which include the decomposition of wood, 21,22 fuel, [23][24][25] plastics, 26,27 incense burning, 28 cooking and deepfrying, [29][30][31][32][33][34] smoking, tobacco heating and vaping. 37,38 The cause of the formation of acrolein during food preparation are the decomposition processes of the fatty acids, 39 glycerides and carbohydrates contained in food.…”
Section: Indoor Emission Sourcesmentioning
confidence: 99%
“…The formation of acrolein is attributed to high-temperature degradation of cooking oil and heated vegetables, respectively. 34 In a Chinese temple, the acrolein level was up to 3 times higher during incense burning than in the outside. 28 Williams et al 51 determined an average acrolein concentration of 5 -6 µg m -³ in 6 London smoking rooms exceeding those measured in comparison rooms.…”
Section: Acrolein Levels In Outdoor and Indoor Airmentioning
confidence: 99%